The Perception of Communication Related Value-Added Educational Activities: A Survey of Graduate Business Students - Barker, Randolph T. and Stowers, Robert H. (Journal of Technical Writing and Communication, 2007)
The purpose of this article is to evaluate value-add methods and activities applied to organizational communication college-level course work. Graduate organizational communication faculty are aware that their classes serve as direct preparation for students entering business and professional careers. The knowledge learned and the skills acquired in these communication classes are abilities that students take with them to the career marketplace. As such, instructors look for ways to extend the boundaries of the classroom beyond the text and traditional instruction. Faculty believe that each method selected adds value to the educational experiences of students. However, do these methods and activities truly add value to the educational experience as the instructors hope they will? Furthermore, are specific programs more valuable than others?
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE5MC90dy4zNy4zLmc